Pengembangan Model Permainan Olahraga Freeball pada Pembelajaran Penjas Adaptif Anak Tunagrahita di SLB Se-Kabupaten Kendal - Anung Anindhito, Yoga Lilo (Universitas Negeri Semarang, 2020)
This study aims to develop the Model of Freeball Sports Games in Adaptive Physical Education in SLB in Kendal Regency and to determine the feasibility of Freeball sports game products based on the assessment of adaptive physical experts, modification game experts, and retarded students in SLB. According to Edo Dwi Cahyono in Sugiyono (2011: 297). Research and development methods are methods used to produce certain products, and test the effectiveness of these products. Validation was carried out by adaptive physical material experts, modification game material experts. The developed product was tested for eligibility for mentally retarded students in SLB in Kendal Regency. The results of the study showed that the feasibility level of the Freeball sports game model on adaptive learning for mentally retarded children was assessed: 1) Expert material I at the final stage obtained a value of 87.7% which was included in the